Effects of social restrictions on people with dementia and carers during the pre‐vaccine phase of the COVID‐19 pandemic: Experiences of IDEAL cohort participants. (13th June 2022) - Pentecost, Claire; Collins, Rachel; Stapley, Sally; Victor, Christina; Quinn, Catherine; Hillman, Alexandra; Litherland, Rachael; Allan, Louise; Clare, Linda
Abstract: This qualitative study was designed to understand the impact of social distancing measures on people with dementia and carers living in the community in England and Wales during a period of social restrictions before the COVID‐19 vaccination roll‐out. We conducted 12 semi‐structured interviews with people with dementia aged 50–88 years, living alone or with a partner, and 10 carers aged 61–78 years, all living with the person with dementia. Three of the interviews were with dyads. Participants were recruited during November and December 2020. We used framework analysis to identify themes and elicit suggestions for potential solutions. We identified three interrelated themes. People with dementia experienced a fear of decline in capabilities or mood and attempted to mitigate this. Carers noticed changes in the person with dementia and increased caring responsibilities, and for some, a change in the relationship. Subsequently, reduced confidence in capabilities to navigate a new and hostile environment created a cyclical dilemma of re‐engaging where an inability to access usual activities made things worse. People with dementia and carers experienced neglect and being alone in their struggle, alongside feeling socially excluded during the pandemic, and there was little optimism associated with the upcoming vaccine programme. People found their own solutions to reduce the effects of isolation by keeping busy and being socially active, and practising skills deemed to help reduce the progression of dementia. This and some limited local public initiatives for the general public facilitated feelings of social inclusion. This study adds understanding to existing evidence about the longer‐term experience of social isolation several months into the pandemic. It highlights the importance of health and community groups and suggests how services can find ways to support, include, and interact with people with dementia and carers during and after social restrictions.